Sustainability Reporting of Indian Companies and the Adherence to GRI Disclosure Framework - Shetty, Rakhesh; Ashalatha, K. (Indian Journal of Finance, 2022)
Given that all significant stakeholders expect companies to be transparent with financial and nonfinancial disclosures, companies are under increasing pressure and are also morally obliged to adhere to voluntary disclosure frameworks. In this regard, the GRI disclosure framework (non-financials) has recently attracted a lot of attention, and listed Indian companies are about to comply with this disclosure framework. Accordingly, this study attempted to gain insights into the extent to which recorded Indian companies adhere to the GRI disclosure framework. For this purpose, we captured the sustainability reports of Indian listed companies from the GRI Sustainability Disclosure Database (SDD) for a span ranging from 20 years from 2000 onwards. The results from this study indicated that of the million listed companies in India, only a few (425 companies) submitted their sustainability reports with GRI in compliance with the guidelines. However, another interesting finding is that majority of these compliant companies are long-listed and from the ESSI industry classification. As GRI disclosure compliance gives away companies’ ethical solid governance practices, it is pretty surprising that exceptionally few Indian companies choose to do so consistently. In line with the findings of this study, we discussed practical and research implications.